Interpretation of Surah Al-Fatihah verse 5 in Tafsir Al-Mishbah: Historically Effected Consciousness and the Construction of National Values - Al-Faiz Muhammad Rabbany Tarman; Indal Abror; Riva Ferdiana Nasywa Az Zahra (Universitas Islam Negeri Sunan Kalijaga, 2025)
This study examines the nationalistic interpretation of Surah al-Fatihah, verse 5, in M. Quraish Shihab’s Tafsir Al-Mishbah, highlighting its historical background and transformative implications for the relationship between religion and nationalism in contemporary Indonesia. Unlike classical exegetes who relatively emphasize the theological-ritualistic dimension, Quraish Shihab interprets na’budu as a representation of collective consciousness that transcends individual worship toward social solidarity and national responsibility. This interpretation is explicitly linked to the second principle of Pancasila, namely “Just and Civilized Humanity.”Using Hans-Georg Gadamer’s hermeneutical framework, particularly the concept of historically effected consciousness, this study argues that Quraish Shihab’s interpretation cannot be separated from his historical horizon and ideological consciousness as an Indonesian Muslim intellectual. This study is a qualitative literature review that analyzes primary sources, namely the Al-Mishbah exegesis and other works by Quraish Shihab, supported by relevant secondary literature.The results of the study indicate that Quraish Shihab’s interpretation constitutes a dialogue between the Qur’anic text and the pluralistic social reality of Indonesia. The emphasis on the values of solidarity, humanity, and nationalism is not merely a development of textual meaning but a reflection of an ideological commitment to harmonizing Islamic teachings with the Indonesian framework. This interpretation has transformative implications by reconstructing the relationship between religion and nationalism from a dichotomous paradigm into a mutually reinforcing one. Thus, Quraish Shihab’s interpretation serves not only as an intellectual product but also as an ideological instrument that promotes inclusive religiosity, strengthens social cohesion, and affirms the compatibility between Islam and national identity in the context of contemporary Indonesia.